1987
DOI: 10.1111/j.1095-8339.1987.tb01052.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemical constituents and economic plants of the Euphorbiaceae

Abstract: The chemical constituents and economic plants of the Euphorbiaceae. A chemical review of the different classes of compounds which have been isolated from the Euphorbiaceae (other than the diterpenoids) is given. This includes triterpenoids and related compounds (sterols, alcohols and hydrocarbons), phenolic compounds (flavonoids, lignans, coumarins, tannins, phenanthrenes, quinones, phenolic acids, etc.), alkaloids, cyanogenic glucosides and glucosinolates. A summary of the industrial and medicinal uses of mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 92 publications
0
52
0
3
Order By: Relevance
“…Lipids were the main reserve materials stored in the endosperm. Seeds of species belonging to the family Euphorbiaceae are usually rich in lipids (Rizk, 1987), e.g. castor-bean (Ricinus communis) seeds where the lipid content (Copeland and McDonald, 1995) approaches that found for E. heterophylla.…”
Section: Resultsmentioning
confidence: 99%
“…Lipids were the main reserve materials stored in the endosperm. Seeds of species belonging to the family Euphorbiaceae are usually rich in lipids (Rizk, 1987), e.g. castor-bean (Ricinus communis) seeds where the lipid content (Copeland and McDonald, 1995) approaches that found for E. heterophylla.…”
Section: Resultsmentioning
confidence: 99%
“…5, No. 4;2013 cycloeuphornol and euphorbol backbone (Rizk, 1987). Other minor compounds identified during GCMS analysis include phytol, ergostadiol, hentriacontane, sitastirol aceate, lupeol and hopenone.…”
Section: Phytochemical Screening Using Gcmsmentioning
confidence: 99%
“…3 The literature search revealed that members of the genus Glochidion were known to contain many bioactive compounds, mainly terpenoids, flavonoids, phenolic acids, alkaloids and to a lesser extent cyanogenic glycosides and glucosinolates. 4 But reported studies on Glochidion superbum are more limited than those on other species. Methyl gallate is widely found in many families and species of plants especially in the Acaraceae family.…”
Section: Introductionmentioning
confidence: 99%